2017
DOI: 10.1186/s12885-017-3755-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of abiraterone acetate in chemotherapy-naive patients with metastatic castration-resistant prostate cancer: an Italian multicenter “real life” study

Abstract: BackgroundTo evaluate the safety and efficacy of abiraterone acetate (AA) in the “real life” clinical practice for men with chemotherapy-naïve metastatic castration-resistant prostate.MethodsA consecutive series of patients with mCRPC in 9 Italian tertiary centres treated with AA was collected. Demographics, clinical parameters, treatment outcomes and toxicity were recorded. The Brief Pain Inventory scale Q3 was tracked and patient treatment satisfaction was evaluated. Survival curves were estimated by the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 20 publications
5
37
0
Order By: Relevance
“…To the best of our knowledge, this case series is the largest cohort of patients reported in Asia. The reported OS and PFS of patients in both the CN and PC cohorts are similar to other case series presented in Table …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To the best of our knowledge, this case series is the largest cohort of patients reported in Asia. The reported OS and PFS of patients in both the CN and PC cohorts are similar to other case series presented in Table …”
Section: Discussionsupporting
confidence: 83%
“…The shorter OS reported in the CN patients, when compared to the relevant cohort in the COU‐AA‐302 study, was attributed to the inclusion of older patients with a heavier burden of symptomatic disease . Other retrospective cohort studies have reported a poorer median OS of patients on AAP in real‐world clinical settings and have attributed their findings to patient factors, that is, age, burden of disease, ECOG status, etc …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, numerous therapeutic methods displayed better results in vitro and in vivo experimental models of prostate cancer, only to be unsuccessful in clinical phase study (Tian et al, ). Several agents are estimated and used to prevent prostate cancer, including abiraterone acetate, docetaxel and cabazitaxel (Cindolo et al, ; Oudard et al, ). These medications failed to fully solve the prevention of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…2 Chemical castration by Androgen Deprivation Therapy (ADT) is the main mode of treatment for metastatic prostate cancer, and this involves inhibiting androgen synthesis. 3 Unfortunately, even though patients treated with ADT initially demonstrate high response rates, the cancer will inevitably progress to the final stage in the disease continuum known as metastatic castration-resistant prostate cancer (mCRPC). 4,5 mCPRPC is defined as tumor growth despite testosterone suppression (<50 ng/dL) and is usually followed by death within 24-48 months after development of castration-resistance.…”
Section: Introductionmentioning
confidence: 99%